THE INFLUENCE OF FINANCIAL AND MONETARY VARIABLES ON THE ECONOMIC GROWTH IN POLAND - Visan, Cristina (Economics of Agriculture, 2012)
The paper analyzes if money and other monetary and financial variables cause economic activity using quarterly data from Polish economy starting with 2003 to 2011. I made bivariate models to see if the monetary and financial variables from this country cause the real economic activity in the short term or in the long term and the neutrality hypothesis of money is confirmed.